1+(no)1=3, and more - García Pérez de León, Carmen (Murmurations: Journal of Transformative Systemic Practice, 2025)
A systemic mapping of binary logic can make clear the question of how attempts to counteract binary thinking fail in their intent to produce transformative -second order, in systemic jargon- change. While an approach to transformational change through paradoxical thinking and the creativity of the absurd is not new, it doesn’t seem to have produced news of difference, since binary thinking seems to persist, with ethical implications for the praxis of systemic therapy and its education and training. Indeed, binary mapping, even when critiqued, tends to reinforce itself, creating a strange loop similar to a Moebius strip. Nonetheless, systemic ethics consists of attending to multiple possibilities beyond binary choices, advocating for relational location of responsibility, coherently with an epistemology that conceives the minimal unit of observation as including not only the constituent parts of a system, but also how these interrelate and their contexts of occurrence. I propose, playfully, a formalisation in the form of “1+(no)1=3, and more” emphasizing that relationships and contexts are integral to understanding systems, and the difference between relativism and relationality. I connect this differentiation with a critique of the notion of unity which can be drawn expanding interconnectedness in a totalising fashion often proposed in monotheistic traditions with which some systemic therapists bridge and, arguing that these can lead to all-encompassing theories that overlook individual differences. From such stance, I discus the ethical implications of othering along with limitations of inclusivity and belonging as proposed by equality and diversity in both corporate and governmental policies. Finally, I take on Byng-Hall's notions of life scripts, suggesting that attempts to replicate or correct these scripts often lead to frustration, while improvisation is a feature of therapeutic change, as a way to respond creatively to the kind of life’s challenges that are explored in therapy. I conclude moving to a wider contextual level, by emphasizing the importance of acknowledging both life and decay, arguing against the idea of limitless accumulation and for a more nuanced understanding of systemic relationships.